BOUNDARY ELEMENT METHOD APPLIED TO STEADY PERIODIC HEAT CONDUCTION - Yang, Shi Chao; Zheng, Guo Rong (Numerical heat transfer. Part A, Applications, 1991)
This paper describes implementation of the boundary element method to steady periodic heat-conduction problems. The use of a complex harmonic representation of the solution reduces the time-dependent parabolic partial differential equation to a time-independent Helmholtz equation. A simple numerical example is given, and excellent correlation with the analytical solution is achieved.